2010
DOI: 10.3109/01677060903583994
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serotonin Transporter Promoter Gene Polymorphism (5-HTTLPR) With Depression in Costa Rican Schizophrenic Patients

Abstract: Depression and suicidal behavior are frequently observed in patients with schizophrenia. The serotonin transporter protein regulates serotonergic signaling at synapses and is encoded by a single gene (SLC6A4; Locus Link ID: 6532), located at 17q11.1-q12 with two polymorphic variants (the short and the long allele). The short allele of serotonin transporter gene has been associated with depression and suicidality in individuals who suffered negative life events and with depression in individuals with chronic ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Since OCD is a heterogeneous disorder, its etiology could not be explained by a single gene but rather by a polygenic basis, as well as environmental factors as child abuse and daily life stress in which the 5-HTTLPR genotype could act as a moderator in the development of a psychiatric disease (Caspi et al, 2003;Caspi et al, 2008). It is proposed that the S allele moderates the influence of life stressing events in the onset of depressive symptoms and suicide risk when compared with homozygous carriers of the allele L (Caspi et al, 2003;Contreras et al, 2010), for which our study found an associated increase in autoantibody titers.…”
Section: Discussionsupporting
confidence: 48%
“…Since OCD is a heterogeneous disorder, its etiology could not be explained by a single gene but rather by a polygenic basis, as well as environmental factors as child abuse and daily life stress in which the 5-HTTLPR genotype could act as a moderator in the development of a psychiatric disease (Caspi et al, 2003;Caspi et al, 2008). It is proposed that the S allele moderates the influence of life stressing events in the onset of depressive symptoms and suicide risk when compared with homozygous carriers of the allele L (Caspi et al, 2003;Contreras et al, 2010), for which our study found an associated increase in autoantibody titers.…”
Section: Discussionsupporting
confidence: 48%
“…The short and long allele differentially affects expression (Dolzan et al, ; Han, Park, Na, Kee, & Lee, ; Heils et al, ). This leads to changes in 5‐HT concentration in the synaptic cleft, amygdala volume, and subsequent behavioral characteristics, such as aggression, stress, depression, and suicide in SZ patients (Contreras et al, ; Hung et al, ; Kobiella et al, ). However, the long alleles differ in expression, as the expression of G allele is similar to that of the short allele (Hung et al, ).…”
Section: Serotonin Pathway Genes Associated With Szmentioning
confidence: 99%
“…Furthermore, understanding admixture in this population is essential for disease susceptibility mapping studies, and Costa Rica's population has been extensively studied for psychiatric diseases (Contreras et al 2010;Escamilla et al 2009;Escamilla et al 2007; Walss- Bass et al 2006;Walss-Bass et al 2009), longevity (Castri et al 2011;Castri et al 2009) and other disease studies (Leon et al 1992). …”
mentioning
confidence: 99%